On the identity of Flirtea (Arachnida, Opiliones, Cosmetidae) - Kury, Adriano B.; García, Andrés F. (Zootaxa, 2016)
Flirtea C.L. Koch, 1839, is one of the oldest genera described in Cosmetidae, currently including 30 species mostly from the Andes. Its type species, Cosmetus pictus Perty, 1833, from Brazil, the type material of which is long lost, has since long been misidentified in the literature due to a redescription based on another unrelated species, while the true F. picta was widely known as Flirtea phalerata C.L. Koch, 1840. This unrelated species is here described as Cynorta pictoides sp. nov. Flirtea picta is here redescribed based on abundant material collected in the Brazilian Atlantic Forest biome from Bahia state, and a neotype is designated for its type species. Here, we propose a particular pattern of a white mask blot on the dorsal scutum be called “scaramuccia”, and variation in this pattern is described. Genital morphology of Flirtea picta is described for the first time. Flirtea is rediagnosed and most species currently assigned to Flirtea are suggested to belong to other genera. Cynorta valida Roewer, 1928 and Paecilaema batman Pinto-da-Rocha & Yamaguti, 2013 are newly transferred to Flirtea, yielding the new combinations Flirtea valida and Flirtea batman.